Meningkatkan Kemampuan Guru dalam Menerapkan Model Pembelajaran Stem Melalui Workshop di Sekolah Dasar Negeri 86/X Harapan Makmur Tahun 2019/2020 - Romadlon Romadlon (Universitas Batanghari Jambi, 2020)
This is a classroom action research that aims to improve the ability of teachers to apply STEM learning models in 86 / X Harapan Makmur State Elementary School, School Year 2019/2020. The subject of this study was a teacher at 86 / X Harapan Makmur Public Elementary School, Rantau Rasau District, Tanjung Jabung Timur District, Jambi Province. This class action research was carried out in two cycles, each cycle consisting of two meetings. The initial observation result was 58.56 and the percentage of completeness was only 50%. The results of the evaluation are converted into a recapitulation table of the results of cycle I. The conversion results state that the research has not yet reached the target, it needs to be continued with cycle II. The results of observers in the implementation phase of the second cycle showed that all parts of the learning activities were going well, so that there were no more parts of the learning activities that needed to be improved. While the results of the second cycle are converted with the results of the recapitulation table states that the research has reached the target limit of completeness criteria in the first cycle of 50% and an average of 67.5 in the initial conditions of improvement in the second cycle of completeness criteria to 87.5% and average that is 87.46 states that workshops can improve the ability of teachers to apply the STEM learning model in learning at 86 / X State Elementary Schools Harapan Makmur 2019/2020 Academic Year.